2019
DOI: 10.3390/molecules24193625
|View full text |Cite
|
Sign up to set email alerts
|

Bimodular Antiparallel G-Quadruplex Nanoconstruct with Antiproliferative Activity

Abstract: Oligonucleotides with an antiproliferative activity for human cancer cells have attracted attention over the past decades; many of them have a G-quadruplex structure (GQ), and a cryptic target. In particular, DNA oligonucleotide HD1, a minimal GQ, could inhibit proliferation of some cancer cell lines. The HD1 is a 15-nucleotide DNA oligonucleotide that folds into a minimal chair-like monomolecular antiparallel GQ structure. In this study, for eight human cancer cell lines, we have analyzed the antiproliferativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
(84 reference statements)
1
15
0
Order By: Relevance
“…These are not the unique literature examples of aptamer optimization obtained by dimerization of known aptamer sequences. Indeed, in the last decade a number of works described improved aptamers realized by engineering bivalent or multivalent analogues of the selected oligonucleotide, not only for VEGF, but also for thrombin [19,[22][23][24][25][26][27], mIgM (B-cell receptor) [28,29], and other biologically relevant targets [30][31][32], so that this strategy can be considered among those of choice to increase the overall efficacy of selected aptamers [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…These are not the unique literature examples of aptamer optimization obtained by dimerization of known aptamer sequences. Indeed, in the last decade a number of works described improved aptamers realized by engineering bivalent or multivalent analogues of the selected oligonucleotide, not only for VEGF, but also for thrombin [19,[22][23][24][25][26][27], mIgM (B-cell receptor) [28,29], and other biologically relevant targets [30][31][32], so that this strategy can be considered among those of choice to increase the overall efficacy of selected aptamers [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, it was shown that just the single stranded oligonucleotide extensions at both the 3′- and 5′-ends of GQ of HD1 could affect the GQ properties [ 19 ]. Indeed, for the simplest case, bi-HD1, it seems that the two GQ modules are not equal, being covalently conjugated via single T ([ 14 ], and refs therein). Indeed, the molar ellipticity of CD spectrum at 295 nm of bi-HD1 is not exactly twice as for HD1, but just 1.5 times ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…Originally, 15-mer DNA GQ HD1 ( Figure 1 ) was discovered in 1991 as a thrombin binding aptamer via selection by conventional SELEX [ 13 ]. As HD1 has a typical GQ structure, it exhibits anti-proliferative activity like some other GQs [ 1 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure was redrawn from Kimoto et al 203 [Color figure can be viewed at wileyonlinelibrary.com] strategy. [206][207][208] Several examples are reported, not only for VEGF, but also for thrombin, 185,205,[209][210][211][212][213][214] (B-cell receptor), 215,216 and other biologically relevant targets. [217][218][219] Notably, multimerization can be very easily achieved with nucleic acid-based aptamers through ad hoc synthetic modifications in their oligonucleotide backbones.…”
Section: Dimeric and Multimeric Anti-vegf Dna-based Aptamersmentioning
confidence: 99%